Analysis of Education and Training Levels on Employee Performance at The Girimarto Sub-District Office, Wonogiri Regency - Astrianingsih Astrianingsih; Zandra Dwanita Widodo; Atik Lusia (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
Employee performance is a strategic factor in improving the quality of public services within local government institutions. Education level and job training are considered important determinants in shaping employee competence and professionalism. This study aims to analyze the role of education level and training in relation to employee performance at the Girimarto Sub-District Office, Wonogiri Regency. This research employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observation, and document analysis, and analyzed thematically using NVivo software. Data validity was ensured through source and method triangulation. The findings indicate that educational levels aligned with job duties and functions contribute to improved understanding of work procedures, task accuracy, and employee performance quality. Furthermore, relevant and continuous training enhances technical skills, work discipline, and the quality of public services, although limitations were identified in training frequency and the relevance of training materials. This study emphasizes the importance of structured, sustainable, and needs-based human resource management to support effective public service delivery.